The relationship between isokinetic strength and anaerobic performance in elite youth football players - Hasan Huseyin Yilmaz; Kemalettin Seren; Gokhan Atasever (Ozlem Book Center, 2023)
The purpose of our study was to examine the relationship between isokinetic strength and anaerobic performance in elite youth male football player. Nineteen voluntary athletes were included in the study. All athletes trained in the same football academy. All youth male athletes performed an anthropometric test, anaerobic power test and an isokinetic strength test at 60o/sec angular speed both limbs. Peak torque values were directly obtained from isokinetic dynamometer and Relative Peak Torque values were calculated by dividing peak torque values by body weight of the athlete. The relationships between anaerobic power and isokinetic strength outputs were determined using an analysis of pearson correlation coefficient. The data obtained from the research were shown as mean ± SDs. Peak torque of extensor and flexor muscles in both extremities at 60o/sec. and wingate anaerobic peak power strongly related to each other (p<0.01) and relative peak torque of right knee extensor muscles and anaerobic relative peak power were moderately related to each other (p<0.05); However, the relative peak torque values of left leg extensor muscles and anaerobic relative peak power values have no significant relation (p>0.05). Besides, there was no relationship between the relative peak torques of both leg flexor muscles and anaerobic relative peak power values (p>0.05). Importantly, isokinetic parameters and anaerobic power parameters were highly related in youth elite football players.